2022
DOI: 10.1038/s41598-022-09298-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence challenges the presumed defensive function of a “slow toxin” in cycads

Abstract: Abstract$$\beta$$ β -methylamino-L-alanine (BMAA) is a neurotoxic non-protein amino acid found in the tissues of cycad plants. The demonstrated toxicity of BMAA to diverse organisms, including humans, is widely assumed to imply a defensive function of BMAA against herbivores; however, this hypothesis has not previously been tested in an ecologically relevant system. We investigated the effects of dietary BMAA, across a range of dosages matching and exceeding levels typically p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…leaves are insufficient to deter the generalist herbivore, Spodoptera littoralis (Whitaker et al, 2022). That BMAA is more concentrated in E. atala larvae than adults may indicate that the compound deters predators that specifically target the larval stages (e.g., parasitoids), though our data provide further evidence that BMAA may not be a feeding deterrent to invertebrates, in this case to a different trophic level.…”
Section: Figurementioning
confidence: 56%
See 1 more Smart Citation
“…leaves are insufficient to deter the generalist herbivore, Spodoptera littoralis (Whitaker et al, 2022). That BMAA is more concentrated in E. atala larvae than adults may indicate that the compound deters predators that specifically target the larval stages (e.g., parasitoids), though our data provide further evidence that BMAA may not be a feeding deterrent to invertebrates, in this case to a different trophic level.…”
Section: Figurementioning
confidence: 56%
“…BMAA is a particularly interesting compound due to its toxicity to diverse organisms and its role in human neurodegenerative disease (Cox et al, 2003). Recent work suggests that BMAA may not be an effective anti-herbivore compound for cycads (Whitaker et al, 2022), but its potential as a defensive compound for cycad-feeding insects has never been explored. Eumaeus butterflies and other cycad herbivores encounter BMAA in their larval host plants, which is produced by endophytic cyanobacteria in specialized roots (Banack and Cox, 2003;Cox et al, 2003), but aside from evidence that BMAA is present in the larvae and pupal casings of the cycad-pollinating weevil, Rhopalotria mollis (Vovides et al, 1993), nothing is known about BMAA sequestration by insects.…”
mentioning
confidence: 99%
“…Some cycad-feeding Aulacoscelinae beetles reflexively bleed MAM-glycosides -presumably sequestered from their foodplantswhen disturbed or threatened (Prado et al, 2011), and at least one lepidopteran has been shown to be capable of detoxifying MAM (Teas, 1967). Recently, the obligate cycad herbivore Eumaeus atalabutterfly was found to accumulate BMAA into their larval and adult tissues (Whitaker et al ., 2023), although the defensive value of sequestering BMAA remains questionable given its latent toxicity (Whitaker et al, 2022). Genomic evidence does suggest, however, that toxin tolerance is a key adaptation in the radiation ofEumaeus butterflies, a wholly cycadivorous neotropical genus of six species (Robbins et al, 2021).…”
Section: Parasitic Insect Herbivoresmentioning
confidence: 99%
“…L1 larvae appear to cope better with some other non‐protein amino acids, for example, diaminopropionic acid or homoarginine, which characterise Lathyrus species (Bell, 1972 ) and in which A. obtectus can complete its life cycle (Szentesi, 2021 ). It is important to note, however, that SPMs toxicity may be affected by synergistic and/or antagonistic interactions among different compounds (Janzen et al, 1977 ), highlighting the limitation on conclusions to be drawn from tests with individual compounds (Whitaker et al, 2022 ). Recent approaches to build up Phaseolus resistance to A. obtectus focus on increasing seed APA (arcelin, phytohemagglutinin and α‐amylase inhibitor) protein content (Velten et al, 2008 ; Zaugg et al, 2013 ), which interferes with digestion in different ways (Sales et al, 2000 ).…”
Section: Chemical Ecology In Store House Environmentsmentioning
confidence: 99%